Reflexiones en torno al origen de la creación pictórica de Miquel Barceló - B. Nasini (Bajo Palabra, 2016)
El presente artículo tiene por objeto esclarecer la cuestión del origen de la creación pictórica de Miquel Barceló mediante tres ensayos sucesivos, a saber: (1) la relación dialéctica entre la obra y la experiencia vital del artista; (2) la influencia velada que la lógica del museo ejerce sobre el inconsciente del artista según Groys; (3) la búsqueda del origen de la obra de arte en el propio arte según Heidegger. De entre los tres, nos inclinaremos por este último, que trasciende la biografía y la psicología del artista. Palabras clave: Origen, experiencia vital, nuevo, museo, mundo, tierra. Abstract: The purpose of this article is to clarify the question of the origin of Miquel Barcelo's pictorial creations. We will try to achieve this objective by successively exploring three issues: 1) the dialectical relation between the works of the artist and his own personal life experience, 2) the veiled influence that the logic of the museum exerts on the unconscious of the artist, according to Groys, 3) the search for the origins of the work of art inside same art itself, according to Heidegger. After examining these three issues, we will explain why the third one is the most illuminating, since it goes beyond the biography and the psychology of the artist. Keywords: Origin, work of art, vital experience, new, museum, world, ground.